Mangal Pandey, the true story of an Indian revolutionary - Misra, Amaresh (New Delhi : Rupa & Co., 2005)
On Maçngala Paònòde, d. 1857, Indian nationalist who lead the Sepoy Mutiny, 1857-1858.
Includes bibliographical references and index.
Keywords: Maṅgala Paṇḍe, -- 1857.; Nationalists -- 19th century -- India -- Biography; India -- History -- Sepoy Rebellion, 1857-1858.